''Assessing the Impact of Gender- Based Violence on Family Member's Well- Being in Rhino Camp Refugee Settlement'' Acase Study of Ofua Three Zone Cluster, Terego District. - Betty Leah Nyoku (Uganda Christian University, 2025)
Gender-based violence (GBV) is a pervasive issue in refugee settlements, intensifying the vulnerability of family members. This study will assess the impact of GBV on family members' physical, emotional, and psychological well-being in Rhino Camp Refugee Settlement, specifically in Ofua Three Cluster, Rhino camp refugee settlement in Terego District, Northern Uganda. A mixed-method approach was employed in this study and it involved both Qualitative and quantitative approaches. The study used both the combination of Questionnaire and interview guide to collect the required data about the prevalence, forms, and consequences of Gender Based Violence. The study explored the coping mechanisms employed by the affected family members and the support systems available to them. The findings of this study anticipated to contribute to the understanding of the impacts of GBV's on the family’s well-being in refugee settings. The study would also inform stakeholders on the development of effective GBV frameworks and policies that promote sustainable family well-being and mitigate the consequence of GBV.
Undergraduate